KECANDUAN GAME ONLINE DAN HILANGNYA TANGGUNG JAWAB REMAJA ANALISIS TAFSIR AL-AZHAR QS AL FURQAN AYAT 43-44 : - - Ahmad Yuda Saputra; Budi Suhartawan (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2026)
The phenomenon of online game addiction in adolescents has become a social problem that has an impact on decreasing individual responsibility, both in academic, social, and spiritual aspects. This study aims to analyze the behavior of online game addiction in the perspective of the Qur'an, especially in the Al-Furqan letter 43-44, and examine the implications for the formation of adolescent character. The method used is qualitative research with a library research approach through analysis of relevant verses, by referring to the Tafsir Al-Azhar as the main source. The results of the study show that online game addiction can be understood as a form of uncontrolled lust domination, as described in the interpretation of the verse, where individuals tend to make desires as gods that direct their behavior. This condition has an impact on weakening self-control, reduced awareness of responsibility and a tendency to ignore the main obligations in life. This study emphasizes the importance of religious values, character education, as well as the role of family and the environment in building adolescent self-control. Thus, the use of technology, including online games, can be directed wisely and professionally. Keywords: Online gaming addiction, adolescent responsibility, Al-Azhar Tafsir